Process for preparing carbon from lignin
By immersing lignin in an acidic solution and subsequent heat treatment, the process efficiently removes metals from lignin, producing carbon with low metal content for energy storage applications, enhancing electrochemical performance and scalability.
Patent Information
- Application Number
- CN202380031782.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-04-04
- Filing Date
- 2023-04-03
- Publication Date
- 2024-12-20
AI Technical Summary
Existing methods for producing carbon from lignin are inefficient in removing metals, particularly transition metals like iron and manganese, which can negatively impact the performance of energy storage devices due to their presence in the carbon structure, and are not cost-effective for large-scale manufacturing.
A process involving immersing lignin with a total metal content of less than 200 ppm in an acidic aqueous solution at 40-100°C for at least 15 minutes, followed by separation and optional washing, to achieve carbon with a low metal content suitable for energy storage applications, combined with a heat treatment at 300-1500°C to convert lignin into carbon.
The process effectively reduces metal content in lignin to below 200 ppm, resulting in carbon with improved electrochemical properties and long-term cycle performance, suitable for use in negative electrodes of secondary batteries, while being compatible with large-scale manufacturing.
Smart Images

Figure BDA0005066690370000161
Abstract
Description
Technical Field
[0001] The present invention relates to a method for preparing carbon from lignin, wherein the lignin has a total metal content of less than 200 ppm. In addition, the present invention relates to carbon obtained from lignin and having a total metal content below 800 ppm, which carbon is suitable for use in energy storage applications due to the low metal content. Background Art
[0002] Carbon-enriched materials can be used in various end uses, such as biochar, activated carbon, and energy storage materials.Most carbon-enriched materials today are produced from fossil-based precursors.
[0003] It is expected that lignin will be used as a replacement for fossil-based carbon-containing materials. Lignin (aromatic polymer) is the main component in wood, for example, and is the most abundant carbon source on Earth after cellulose. In recent years, the development and commercialization of technologies for extracting highly purified, solid and particularized forms of lignin from pulping processes has attracted great attention as a possible renewable substitute for the main aromatic chemical precursors currently derived from the petrochemical industry.
[0004] One use of carbon-enriched materials is as a negative electrode in secondary batteries such as lithium-ion batteries. Graphite (natural or synthetic graphite) is now routinely used as a material for the negative electrode in most lithium-ion batteries. Alternatives to graphite are amorphous carbon materials, such as hard carbon (non-graphitizable amorphous carbon) and soft carbon (graphitizable amorphous carbon), which lack long-range graphitic order. Amorphous carbon can be used as a single active electrode material or mixed with graphite (and / or other active materials) and can be derived from lignin. Amorphous carbon derived from lignin is typically non-graphitizable, i.e., hard carbon.
[0005] Nowadays, the most commercially relevant source of lignin is kraft lignin. This lignin is obtained from hardwood or softwood by the kraft process. The lignin can be separated from alkaline black liquor using, for example, membrane filtration or ultrafiltration. LignoBoost is a conventional separation process and is described in, for example, WO2006031175A1. In this process, lignin is precipitated from alkaline black liquor by reducing the pH level (usually by adding carbon dioxide) and then filtered out. In the next step, the lignin filter cake is re-pulped (usually using sulfuric acid) and washed under acidic conditions. The precipitated washed lignin can be used directly or further dried.
[0006] Black liquor is readily available as a byproduct from the kraft process and is thus a cost-effective source of lignin. However, since black liquor contains a certain amount of metals, mostly derived from wood and from the cooking chemicals used during the pulping process, the lignin precipitated from the black liquor will also contain a certain amount of metals. Typically, lignin will contain relatively high levels of sodium and potassium and lower amounts of other metals such as aluminum, calcium, iron, magnesium and manganese. Lignin may also contain trace amounts of other metals.
[0007] Some metals, such as sodium and potassium, can be removed to a large extent from the precipitated lignin by an acidic washing step during the separation process. However, other metals, such as iron, are more difficult to remove from the precipitated lignin.
[0008] For carbon-enriched materials used in applications such as energy storage applications, there are strict purity requirements. It is therefore important that the purity level of lignin used to prepare carbon intended for those applications is sufficiently high. In particular, the metal content of the lignin needs to be sufficiently low. Any metal present in the lignin will remain after carbonization, and thus also be present in the carbon-enriched material. The metal may, for example, interfere with the functionality of the carbon-enriched material, such as electrochemical properties and long-term cycle performance. Specifically, if present in energy storage applications involving carbon-enriched materials obtained from lignin, transition metals such as iron and manganese may have a negative impact on the long-term stability of the energy storage device. It is believed that this is caused by the precipitation of transition metals during charging and discharging, and also by the decomposition of electrolytes that react through transition metal catalysis.
[0009] In addition, the metals present during the carbonization of the lignin may also catalyze processes that result in changes in the structure of the resulting carbon-enriched material. Maintaining the carbon structure is particularly important when the carbon-enriched material is intended for use in applications such as energy storage devices and capacitors, where the carbon structure is important for achieving proper functioning of the device.
[0010] Lignin can also be obtained by different fractionation methods such as organosolv process or hydrolysis of lignin.However, the commercial interest of organosolv process for producing lignin is lower compared to kraft process.
[0011] Various attempts to remove metals from lignin have been made. Common to these methods is that they are quite complex, involving many additional processing steps; and / or they are not sufficiently efficient in their metal removal efficiency resulting in insufficient purity levels and / or long washing times.
[0012] KR101451299 B1 discloses a method in which lignin is repeatedly dissolved and precipitated to obtain lignin with a low ash content. However, many additional process steps are required.
[0013] WO2020013752 A1 discloses a method for dissolving lignin in an acidic aqueous solvent. A two-phase system is obtained by phase separation, in which one phase is a lignin-rich phase and the other phase lacks lignin and contains metal cations extracted from lignin. However, many additional process steps are required.
[0014] Thus, there is a need for an improved process for preparing carbon having a sufficiently low metal content to make the carbon suitable for use in energy storage applications. Furthermore, the process should be cost-effective and compatible with large-scale manufacturing. Summary of the invention
[0015] It is an object of the present invention to provide an improved process for producing carbon from lignin which obviates or mitigates at least some of the disadvantages of prior art processes.
[0016] It is a further object of the present invention to provide a process for preparing carbon from lignin, wherein the carbon has a sufficiently low metal content to make it suitable for use in energy storage applications, such as hard carbon active materials in the negative electrode of secondary batteries such as lithium ion batteries.
[0017] It is a further object of the present invention to provide a process for preparing purified carbon from lignin which is compatible with large-scale manufacturing.
[0018] The above-mentioned objects and other objects that those skilled in the art will appreciate based on the present invention are achieved through various aspects of the present invention.
[0019] According to a first aspect, the present invention relates to a method for preparing carbon, wherein the method comprises the following steps:
[0020] i) providing lignin having a total metal content of less than 200 ppm;
[0021] ii) subjecting said lignin to a heat treatment at one or more temperatures in the range from 300°C and 1500°C, wherein said heat treatment is carried out for a total time of from 30 minutes to 10 hours, to obtain carbon.
[0022] The method of the invention according to the first aspect is based on the surprising recognition that carbon suitable for use in energy storage applications can be achieved by carbonization of lignin having a total metal content of less than 200 ppm. Due to the low metal content in the lignin, the metal content in the carbon obtained from the lignin is also low. In particular, the iron and / or manganese content in the obtained carbon is low.
[0023] The lignin having a total metal content of less than 200 ppm is preferably obtained by a process comprising the steps of:
[0024] a) providing lignin in solid form;
[0025] b) providing an acidic aqueous solution having a pH below 6;
[0026] c) immersing the lignin in the acidic aqueous solution for at least 15 minutes, wherein the temperature of the acidic aqueous solution during immersion is in the range of from 40° C. to 100° C., to remove metals from the lignin into the acidic aqueous solution, so as to obtain the purified lignin having a total metal content of less than 200 ppm;
[0027] d) separating the obtained purified lignin from the acidic aqueous solution; and
[0028] e) optionally washing the separated purified lignin
[0029] Therein the lignin remains in solid form during all steps of the process.
[0030] It has surprisingly been found that metals can be removed from lignin by immersing the lignin in an acidic aqueous solution at a temperature in the range of from 40°C to 100°C for at least 15 minutes. This enables a method for purifying lignin which is fast and includes few additional method steps. The method is thus compatible with large-scale production.
[0031] According to a second aspect, the present invention relates to carbon obtained from lignin, wherein the carbon has a total metal content of less than 400 ppm.
[0032] The carbon according to the second aspect can be preferably used in energy applications, such as an active material in a negative electrode of a secondary battery. The low content of metal in the carbon provides improved electrochemical properties, such as charge / discharge capacity and long-term cycle performance.
[0033] According to a third aspect, the present invention relates to a negative electrode for a non-aqueous secondary battery comprising, as an active material, carbon obtainable by the method according to the first aspect.
[0034] According to a fourth aspect, the invention relates to the use of carbon obtainable by the process according to the first aspect as active material in the negative electrode of a secondary battery, such as a lithium ion battery. DETAILED DESCRIPTION
[0035] Throughout this specification the term "lignin" is intended to refer to any type of lignin that can be used as a carbon source for making carbon materials. Examples of such lignins are, but are not limited to, lignins obtained from plant raw materials such as wood, e.g., softwood lignin, hardwood lignin, and lignin from annular plants. Lignin may also be chemically modified.
[0036] Preferably, the lignin has been purified or separated before being used in the process according to the invention. Lignin may be separated from black liquor and optionally further purified before being used in the process according to the invention. Purification typically results in a lignin purity of at least 90%, preferably at least 95%, more preferably at least 98%, based on the dry weight of the lignin material. Thus, the lignin material used in the process according to the invention preferably contains less than 10%, preferably less than 5%, more preferably less than 2% impurities, such as cellulose, carbohydrates and inorganic compounds, based on the dry weight of the lignin material.
[0037] Lignin can be obtained by different fractionation methods such as an organosolv process or a kraft process. Preferably, the lignin used in the method of the present invention is kraft lignin, i.e. lignin obtained by a kraft process. Preferably, the kraft lignin is obtained from hardwood or softwood, most preferably from softwood.
[0038] Lignin can be obtained by using a process commonly referred to as the LignoBoost process disclosed in WO2006031175 A1. Typically, the process involves the steps of precipitation of lignin from alkaline black liquor by acidification; separation of the precipitated lignin; and re-slurrying the lignin at least once under acidic conditions. The obtained lignin can be dried and pulverized and thus provided as solid particles. The lignin obtained by this method typically has a total metal content in the range of from 500 ppm to 5000 ppm, mainly derived from wood sources and cooking chemicals added during the pulping process. The pH of the obtained lignin is typically in the range of from 3 to 4, and the sulfur content is typically about 1-3% by weight.
[0039] According to the step i of the method for the first aspect) it is related to providing a lignin with a total metal content of less than 200ppm. As used herein, the term "total metal content" refers to the total amount of metals present in the lignin. Typically, these metals are sodium, potassium, magnesium, calcium, aluminum, iron and manganese. Other metals may also be present in trace amounts. The metal content can be determined by the inorganic element analysis using inductively coupled plasma emission spectroscopy (ICP-OES). The total metal content is determined by summing up the amount of all individual metals. According to the step i of the method for the first aspect of the present invention, the lignin provided has a total metal content of less than 200ppm, preferably less than 150ppm and more preferably less than 100ppm.
[0040] The lignin provided in step i) of the method according to the first aspect may further have an iron content of less than 15 ppm, preferably less than 10 ppm.
[0041] The lignin provided in step i) of the method according to the first aspect may further have a manganese content of less than 10 ppm, preferably less than 6 ppm.
[0042] The lignin provided in step i) of the method according to the first aspect may also have an aluminum content of less than 17 ppm, or less than 13 ppm; a calcium content of less than 16 ppm, or less than 10 ppm; a potassium content of less than 10 ppm, or less than 5 ppm; a magnesium content of less than 42 ppm, or less than 25 ppm; and a sodium content of less than 30 ppm, or less than 15 ppm.
[0043] In an alternative embodiment, the lignin provided in step i) of the method according to the first aspect may have a total metal content in the range from 0 to 200 ppm, such as from 0.1 to 200 ppm, preferably in the range from 0 to 150 ppm, such as from 0.1 to 150 ppm, and more preferably in the range from 0 to 100 ppm, such as from 0.1 to 100 ppm.
[0044] In alternative embodiments, the lignin provided in step i) of the method according to the first aspect may have an iron content in the range from 0 to 15 ppm, or from 0 to 10 ppm, or from 0.1 to 15 ppm, or from 0.1 to 10 ppm.
[0045] In alternative embodiments, the lignin provided in step i) of the method according to the first aspect may have a manganese content in the range from 0 to 10 ppm, or from 0 to 6 ppm, or from 0.1 to 10 ppm, or from 0.1 to 6 ppm.
[0046] In alternative embodiments, the material provided in step i) may have an aluminum content in the range of from 0 to 17 ppm, or from 0 to 13 ppm; a calcium content in the range of from 0 to 16 ppm, or from 0 to 10 ppm; a potassium content in the range of from 0 to 10 ppm, or from 0 to 5 ppm; a magnesium content in the range of from 0 to 42 ppm, or from 0 to 25 ppm; and a sodium content in the range of from 0 to 30 ppm, or from 0 to 15 ppm.
[0047] In alternative embodiments, the lignin provided in step i) may have an aluminum content in the range of from 0.1 to 17 ppm, or from 0.1 to 13 ppm; a calcium content in the range of from 0.1 to 16 ppm, or from 0.1 to 10 ppm; a potassium content in the range of from 0.1 to 10 ppm, or from 0.1 to 5 ppm; a magnesium content in the range of from 0.1 to 42 ppm, or from 0.1 to 25 ppm; and a sodium content in the range of from 0.1 to 30 ppm, or from 0.1 to 15 ppm.
[0048] The lignin provided in step i) of the method according to the first aspect may further have a silicon content of less than 80 ppm, such as in the range from 0 to 80 ppm, or from 0.1 to 80 ppm.
[0049] The lignin provided in step i) of the method according to the first aspect is in solid form, i.e. it is not in a dissolved state. Preferably, the lignin provided in step i) of the method according to the first aspect is in the form of particles, such as in the form of a powder. The particle size distribution of the lignin particles is preferably such that at least 80% by weight of the particles have a diameter of less than 0.2 mm. In the context of the present invention, if the particles are not spherical, the diameter of the particles is the equivalent spherical diameter of the particles. The equivalent spherical diameter is the diameter of a sphere of equivalent volume.
[0050] The lignin having a total metal content of less than 200 ppm provided in step i) of the method according to the first aspect is preferably obtained by a method for purifying lignin comprising the steps of:
[0051] a) providing lignin in solid form;
[0052] b) providing an acidic aqueous solution having a pH below 6;
[0053] c) immersing the lignin in the acidic aqueous solution for at least 15 minutes, wherein the temperature of the acidic aqueous solution during immersion is in the range of from 40° C. to 100° C., to remove metals from the lignin into the acidic aqueous solution, so as to obtain the purified lignin having a total metal content of less than 200 ppm;
[0054] d) separating the obtained purified lignin from the acidic aqueous solution; and
[0055] e) optionally washing the separated purified lignin
[0056] Therein the lignin remains in solid form during all steps of the process.
[0057] The lignin provided in step a) of the method for purifying lignin is in solid form, i.e. it is not in a dissolved state. The lignin can be provided in the form of a dry powder. Alternatively, the lignin can be wet or provided in a slurry or suspension. The lignin can also be provided as a crushed lignin cake obtained from a lignin separation process. During any step in the method for purifying lignin, the lignin does not dissolve, but remains in solid form.
[0058] Alternatively, during the steps of the method according to the invention, the lignin may be dissolved to a small extent, so that only small fragments of solid lignin are dissolved. Thus, the lignin will remain mainly in a solid state. Any dissolved lignin will be removed during the separation step and discarded from the process.
[0059] The lignin provided in step a) of the method for purifying lignin may have a total metal content of at least 500 ppm, preferably at least 600 ppm and more preferably at least 700 ppm. In another embodiment, the lignin provided in step a) of the method for purifying lignin has a total metal content in the range of from 500 ppm to 5000 ppm, preferably from 600 ppm to 3000 ppm, and more preferably from 700 ppm to 1500 ppm.
[0060] In an alternative embodiment, the lignin provided in step a) of the method for purifying lignin may have an aluminum content of at least 18 ppm or at least 19 ppm; a calcium content of at least 18 ppm or at least 19 ppm; an iron content of at least 16 ppm or at least 17 ppm; a potassium content of at least 30 ppm or at least 50 ppm; a magnesium content of at least 45 ppm or at least 48 ppm; a manganese content of at least 11 ppm or at least 12 ppm; and a sodium content of at least 400 ppm or at least 650 ppm.
[0061] In an alternative embodiment, the lignin provided in step a) of the method for purifying lignin may have an aluminum content in the range of from 18 to 25 ppm, preferably from 19 to 23 ppm; a calcium content in the range of from 18 to 40 ppm, preferably from 19 to 25 ppm; an iron content in the range of from 16 to 30 ppm, preferably from 17 to 22 ppm; a potassium content in the range of from 30 to 90 ppm, preferably from 50 to 70 ppm; a magnesium content in the range of from 45 to 55 ppm, preferably from 48 to 53 ppm; a manganese content in the range of from 11 to 30 ppm, preferably from 11 to 16 ppm; and a sodium content in the range of from 400 ppm to 2000 ppm, preferably from 650 to 1000 ppm.
[0062] Step b) of the method for purifying lignin involves providing an acidic aqueous solution having a pH below 6. The term "acidic aqueous solution" as used herein refers to any type of aqueous solution having a pH below 7. The acidic aqueous solution in step b) of the method for purifying lignin can be provided by adding at least one acid to the aqueous solution. The pH of the acidic aqueous solution provided in step b) of the method for purifying lignin has a pH below 6, preferably below 5 and more preferably below 4. In an alternative embodiment, the pH of the acidic aqueous solution may be below 7. In yet another alternative embodiment, the pH of the acidic aqueous solution may be in the range of from 1 to 6, preferably from 2 to 5, and more preferably from 1 to 4.
[0063] Lignin can be added to the aqueous solution after the acid has been added. Alternatively, lignin can be added to the aqueous solution before the acid is added. Or the aqueous solution is heated before the addition of acid and lignin or after the addition of acid and lignin. In one embodiment, acid is added to the heated aqueous solution and lignin is subsequently added to the heated aqueous solution. In another embodiment, lignin is added to the acidic aqueous solution and then heated. In yet another embodiment, acid is added to the aqueous solution containing lignin. In this embodiment, the aqueous solution is heated before or after the addition of acid. In a preferred embodiment, lignin is added to the heated aqueous solution and acid is subsequently added to the aqueous solution containing lignin.
[0064] The acidic aqueous solution provided in step b) of the method for purifying lignin comprises at least one acid such that the pH of the acidic aqueous solution is below 7, or below 6, or below 5, or below 4. In a preferred embodiment, the acidic aqueous solution comprises at least one organic acid. The organic acid may be a carboxylic acid and may be monoprotic, diprotic or triprotic. In a preferred embodiment, the organic acid has a pKa value equal to or less than 4.75 for at least one acidic group. The organic acid may be selected from at least one of acetic acid, citric acid, formic acid and oxalic acid. Preferably, the acidic aqueous solution comprises at least one organic acid selected from formic acid and oxalic acid. It has been found that the use of organic acids further reduces the metal content in lignin during the immersion step. Compared with acids containing sulfur, nitrogen and / or phosphorus, organic acids such as formic acid and oxalic acid are cheap, easy to handle, have low toxicity and are generally less subject to certain waste disposal regulations.
[0065] In alternative embodiments, the acidic aqueous solution comprises at least one inorganic acid such as sulfuric acid, hydrochloric acid, or phosphoric acid.
[0066] The acidic aqueous solution may also contain more than one acid, such as a combination of two or more organic acids or inorganic acids. The acidic aqueous solution may also contain a combination of organic acids and inorganic acids. In one embodiment, the acidic aqueous solution contains both formic acid and oxalic acid.
[0067] In one embodiment, the total amount of acid in the acidic aqueous solution can be in the range of from 0.1 to 6 weight %, preferably from 0.5 to 5 weight %, based on the total dry weight of the lignin added to the acidic aqueous solution. As used herein, the term "total amount of acid" refers to the total amount of concentrated acid added to the acidic aqueous solution. Increasing the amount of acid can increase the removal of metal from lignin. However, it is beneficial to avoid using a large amount of acid from the perspective of technology, for cost reasons and because it is conducive to waste treatment. By increasing the amount of acid in the acidic aqueous solution, the side reaction of degradable lignin can also be triggered.
[0068] The acidic aqueous solution may further comprise one or more additives. The additive may be a dispersant, such as glycerol or a fatty acid. The additive may also be an oxidant such as hydrogen peroxide or EDTA. Other additives include ion exchangers such as ammonium salts such as ammonium acetate and ammonium sulfate. The additives in the acidic aqueous solution may enhance the effect of removing metals from lignin.
[0069] Step c) of the method for purifying lignin involves immersing the lignin particles in an acidic aqueous solution for at least 15 minutes, wherein the temperature of the acidic aqueous solution during immersion is in the range from 40°C to 100°C to remove metals from the lignin into the acidic aqueous solution so as to obtain said purified lignin.
[0070] The term "immersion" as used herein refers to a process in which lignin in solid form (such as in the form of lignin particles) is contacted with an acidic aqueous solution for a certain period of time. During the immersion step of the method for purifying lignin, the entire surface area of the lignin is contacted with the acidic aqueous solution, meaning that the lignin is completely immersed in the acidic aqueous solution.
[0071] Lignin is immersed in an acidic aqueous solution at a temperature in the range of from 40°C to 100°C, such as from 50°C to 90°C or from 60°C to 80°C. In one embodiment, lignin is immersed in an acidic aqueous solution at a temperature in the range of from 40°C to 110°C, such as from 80°C to 100°C. The acidic aqueous solution can be heated in any suitable manner known to those skilled in the art. The temperature is maintained in a defined range during the entire immersion step. The metal removal efficiency is improved by heating the acidic aqueous solution. However, if too high a temperature is used, the lignin may be damaged or degraded.
[0072] The immersion time in step c) is at least 15 minutes, preferably at least 30 minutes or even more preferably at least 1 hour. In alternative embodiments, the immersion time is in the scope of from 15 minutes to 6 hours, preferably in the scope of from 30 minutes to 5 hours or even more preferably in the scope of from 1 hour to 4 hours. The metal removal efficiency can be improved by increasing the immersion time. However, in order to be able to realize a cost-effective method that can be easily scaled up, it is important to have a relatively short immersion time. However, the immersion time must be long enough for fully removing metal from lignin.
[0073] Preferably, the acidic aqueous solution is stirred during immersion. Any suitable stirring means as known to those skilled in the art may be used.
[0074] During the immersion step, metal is removed from lignin to an acidic aqueous solution so as to obtain purified lignin. As used herein, the term "purified lignin" refers to a lignin that essentially only comprises lignin, such as lignin based on the dry weight of lignin material at least 99% by weight and other components such as cellulose, carbohydrates and inorganic compounds based on the dry weight of lignin material less than 1% by weight. In particular, the metal of the purified lignin comprises a reduced amount so that the purified lignin has a total metal content of less than 200ppm, preferably less than 150ppm and more preferably less than 100ppm. As mentioned above, lignin is not dissolved during the immersion step, which means that metal is removed from solid lignin and is not removed from dissolved lignin. Thus, the purified lignin obtained is also in solid form, such as in the form of particles.
[0075] Step d) of the method for purifying lignin involves separating the obtained purified lignin having a total metal content of less than 200 ppm from an acidic aqueous solution. The purified lignin is in solid form during separation. The term "separation" as used herein refers to a process for separating lignin from an acidic aqueous solution.
[0076] In a preferred embodiment, separation is carried out by filtration. Alternatively, separation can be carried out by centrifugation or sedimentation or any other suitable means known to those skilled in the art. Since the purified lignin is separated from the acidic aqueous solution, the pH of the acidic aqueous solution and the lignin during the separation step will be the same as the pH during the immersion step. Thus, during the step of separating the purified lignin, the pH of the aqueous acidic solution is below 6, preferably below 5, or more preferably below 4. In one embodiment, the pH of the aqueous acidic solution can be in the range of from 1 to 7, preferably from 2 to 6, more preferably from 2 to 5, and most preferably from 2 to 4.
[0077] In one embodiment of the method for purifying lignin, the steps of immersion and separation are repeated at least once. In this embodiment, before the second separation step, the separated lignin is immersed in an acidic aqueous solution for the second time. The pH, temperature and time of the acidic aqueous solution during the immersion step are selected as discussed above. In an embodiment in which the immersion and separation steps are repeated, parameters such as pH, temperature and time during the immersion can be the same in all different immersion steps or they can vary between different immersion steps. In one embodiment, the same parameters are used during two immersion steps. In one embodiment, the pH in the second immersion step can be lower than the pH in the first immersion step. In another embodiment, the immersion time in the second immersion step can be shorter than the immersion time in the first immersion step. In yet another embodiment, the temperature in the first immersion step can be higher than the temperature in the second immersion step. The total immersion time is the sum of the immersion times for a single step. Separation is preferably carried out by filtration after each immersion step. The metal content of lignin can be further reduced by adding additional immersion steps and by optimizing the parameters of each step such as time, temperature and pH.
[0078] Step e) of the method for purifying lignin involves optionally washing the separated purified lignin. In one embodiment, the separated purified lignin is washed with an aqueous washing solution. The aqueous washing solution is preferably water. In one embodiment, the separated purified lignin is washed with water until the pH of the water used for washing becomes neutral.
[0079] The method for purifying lignin may include an additional step of drying the separated and optionally washed purified lignin. After the separation step or after the optional washing step, the purified lignin obtained is dried with a metal content below 200ppm. The drying of the purified lignin is carried out by methods and equipment known in the art. The temperature during drying is preferably in the range of from 60°C to 160°C, more preferably in the range of from 100°C to 120°C. Drying can be carried out under reduced pressure or vacuum. Preferably, the moisture content of the purified lignin after drying is less than 10% by weight, preferably less than 5% by weight.
[0080] During the immersion step, other inorganic impurities such as silicon may also be removed from the lignin to the acidic aqueous solution. Thus, in one embodiment of the method according to the first aspect, silicon is also removed from the lignin to the acidic aqueous solution during the immersion step; and the purified lignin obtained has a silicon content of less than 80 ppm, such as in the range of from 0 to 80 ppm, or from 0.1 to 80 ppm.
[0081] The purified lignin obtained may be optionally further processed before heat treatment. These further processing steps may involve further washing steps and heating steps. An optional treatment involves compacting the purified lignin in powder form into lignin aggregates, which may be subsequently heat stabilized to obtain heat-stabilized agglomerated lignin. A method for obtaining such heat-stabilized agglomerated lignin is described in WO2021250604 A1.
[0082] Briefly, the purified and preferably dried lignin powder is compacted, and the compacted lignin is pulverized to obtain agglomerated lignin. The compaction of lignin is preferably carried out by roller compaction. An intermediate product is generated in the compaction step. Herein, fine lignin powder is usually fed by a feed hopper and conveyed to a compaction zone by a horizontal or vertical feed screw, where the material is compacted into flakes by a compaction roller with a defined gap. By controlling the feed screw speed, the pressure development in the compaction zone, a flake with uniform density can be obtained. The pressure development in the compaction zone can preferably be monitored and controlled by the rotation speed of the compaction roller. As the powder is dragged between the rollers, it enters a region known as the nip area, where the density of the material increases and the powder is converted into flakes or ribbons. The roller used has a cavity. The depth of each cavity used in the roller compaction is from 0.1mm to 10mm, preferably from 1mm to 8mm, more preferably from 1mm to 5mm or from 1mm to 3mm. The specific pressure applied during compaction may vary, depending on the equipment used for compaction, but may range from 1 kN / cm to 100 kN / cm. Suitable equipment for performing compaction is known in the art.
[0083] In the comminution step, the intermediate product from the compaction step is subjected to comminution or grinding, such as by a rotary granulator, a cage mill, a beater mill, a hammer mill or a pulverizer mill and / or a combination thereof. During this step, further intermediate products are generated.
[0084] After comminution, the comminuted material is preferably subjected to a screening step to remove fine material. In addition, large materials such as agglomerates having a diameter greater than 5.0 mm can be removed and / or recirculated back to the comminution step.
[0085] Agglomerated lignin can also be heat stabilized by heat treatment. In order to produce the heating of heat stabilized agglomerated lignin, the agglomerated lignin is heated to a temperature in the range of from 140 to 250°C, preferably from 180 to 230°C. The heating is carried out for at least 1.5 hours, i.e., the residence time of the agglomerated lignin in the device for heating is at least 1.5 hours. Preferably, the heating is carried out for less than 12 hours. The heating can be carried out at the same temperature throughout the heating step or can be carried out at a variable temperature, such as a gradual increase in temperature or using a temperature gradient. More preferably, the heating is carried out so that the agglomerated lignin is first heated to a temperature of from 140 to 175°C for a period of at least one hour, and then heated to a temperature of from 175 to 250°C for at least one hour.
[0086] By subjecting the lignin to treatments such as agglomeration and thermal stabilization, the lignin will be less susceptible to melting / swelling and changes in size during subsequent thermal treatments.
[0087] In step ii) of the method according to the first aspect of the invention, lignin having a metal content of less than 200 ppm is subjected to a heat treatment at one or more temperatures in the range from 300°C to 1500°C, wherein the heat treatment is carried out for a total time of from 30 minutes to 10 hours, to obtain a carbon material.
[0088] The term "heat treatment" as used herein refers to a process of heating lignin at one or more temperatures and for a sufficient time to convert the lignin into carbon. Depending on the temperature during the heat treatment, different types of carbon, such as charcoal or hard carbon, can be obtained from lignin.
[0089] Preferably, the heat treatment comprises a preliminary heating step, preferably followed by a final heating step. The preliminary heating step is preferably carried out at a temperature between 300 and 800° C., such as between 500 and 700° C., under an inert atmosphere, preferably a nitrogen atmosphere. The duration of the preliminary heating step is at least 30 minutes and preferably less than 10 hours. The preliminary heating step and the final heating step can be carried out as discrete steps or as a single step in direct sequence. The surface area of the product obtained after the preliminary heating step is typically from 300 to 700 m 2 / g range according to BET measurement using nitrogen.
[0090] The final heating step is preferably carried out at a temperature between 800° C. and 1500° C. in an inert atmosphere, preferably a nitrogen atmosphere. The duration of the final heating step is at least 30 minutes and preferably less than 10 hours. After the final heating step is carried out at a temperature of 1000° C. or higher, the surface area of the product obtained is typically 50 m 2 / g or less.
[0091] Preferably, the heat treatment is performed stepwise. Preferably, preliminary heating starts at about 300°C and is subsequently increased to about 500°C. The final heating step is preferably performed between 900°C and 1300°C, such as at about 1000°C.
[0092] Any metal present in lignin will also remain after the conversion to carbon, and thus be present in the carbon obtained. The weight of lignin can be reduced by the conversion to carbon, but the weight of any metal present is not affected by thermal treatment to any significant extent. Thus, compared with the total metal content in lignin (carbon is obtained from the lignin), the total metal content measured by weight in the carbon can increase. In one embodiment, the carbon obtained has a total metal content of less than 800ppm such as less than 600ppm, or less than 400ppm, or less than 200ppm.
[0093] The metals in the carbon may not only originate from the lignin starting material, but may also be due to contamination during the process of conversion of the lignin to carbon.
[0094] In an embodiment, the obtained carbon has a total metal content in the range from 0 to 800 ppm, such as from 0.1 to 800 ppm, or in the range from 0 to 600 ppm, such as from 0.1 to 600 ppm, or in the range from 0 to 400 ppm, such as from 0.1 to 400 ppm, or from 0 to 200 ppm, such as from 0.1 to 200 ppm.
[0095] In one embodiment, the obtained carbon has an iron content of less than 60ppm, such as less than 40ppm or less than 25ppm. In one embodiment, the obtained carbon has an iron content in the range of from 0 to 60ppm, such as from 0 to 40ppm or from 0 to 25ppm. In one embodiment, the obtained carbon has an iron content in the range of from 0.1 to 60ppm, such as from 0.1 to 40ppm or from 0.1 to 25ppm. Carbon with such a low content of iron is advantageous for use as an active material in the negative electrode of a secondary battery, because a high content of iron can have a negative effect on electrochemical properties such as long-term cycle performance.
[0096] In one embodiment, the obtained carbon has a manganese content of less than 40ppm, such as less than 30ppm or less than 20ppm. In one embodiment, the obtained carbon has a manganese content in the range of from 0 to 40ppm, such as from 0 to 30ppm or from 0 to 20ppm. In one embodiment, the obtained carbon has a manganese content in the range of from 0.1 to 40ppm, such as from 0.1 to 30ppm or from 0.1 to 20ppm. Carbon with such a low content of manganese is advantageous for use as an active material in the negative electrode of a secondary battery, because a high content of manganese can have a negative effect on electrochemical properties such as long-term cycle performance.
[0097] In one embodiment, the obtained carbon has an aluminum content of less than 70 ppm, such as less than 50 ppm or less than 30 ppm; a calcium content of less than 60 ppm, such as less than 50 ppm or less than 30 ppm; a potassium content of less than 40 ppm, such as less than 30 ppm or less than 20 ppm; a magnesium content of less than 170 ppm, such as less than 130 ppm or less than 90 ppm; and a sodium content of less than 120 ppm, such as less than 90 ppm or less than 60 ppm.
[0098] In one embodiment, the obtained carbon has an aluminum content in the range of from 0 to 70 ppm, such as from 0 to 50 ppm or from 0 to 30 ppm; a calcium content in the range of from 0 to 60 ppm, such as from 0 to 50 ppm or from 0 to 30 ppm; a potassium content in the range of from 0 to 40 ppm, such as from 0 to 30 ppm or from 0 to 20 ppm; a magnesium content in the range of from 0 to 170 ppm, such as from 0 to 130 ppm or from 0 to 90 ppm; and a sodium content in the range of from 0 to 120 ppm, such as from 0 to 90 ppm or from 0 to 60 ppm.
[0099] In an embodiment, the obtained carbon may have an aluminum content in the range of from 0.1 to 70 ppm, such as from 0.1 to 50 ppm or from 0.1 to 30 ppm; a calcium content in the range of from 0.1 to 60 ppm, such as from 0.1 to 50 ppm or from 0.1 to 30 ppm; a potassium content in the range of from 0.1 to 40 ppm, such as from 0.1 to 30 ppm or from 0.1 to 20 ppm; a magnesium content in the range of from 0.1 to 170 ppm, such as from 0.1 to 130 ppm or from 0.1 to 90 ppm; and a sodium content in the range of from 0.1 to 120 ppm, such as from 0.1 to 90 ppm or from 0.1 to 60 ppm.
[0100] The resulting carbon may have a silicon content of less than 320 ppm, such as less than 240 ppm, or less than 160 ppm.
[0101] The obtained carbon material may be subjected to other treatments such as crushing, classification, coating and further heat treatment.
[0102] According to a second aspect, the present invention relates to a carbon having a total metal content of less than 800ppm, such as less than 600ppm, or less than 400ppm, or less than 200ppm. The carbon is obtained by a method according to the first aspect. Due to the low metal content of the carbon, it is suitable for use in active materials in energy storage applications such as negative electrodes of secondary batteries. The carbon according to the second aspect may be further limited as described above with respect to the first aspect.
[0103] According to a third aspect, the present invention relates to a negative electrode for a non-aqueous secondary battery comprising as active material a carbon obtainable by the method according to the first aspect. The carbon according to the third aspect may be further defined as set out above in relation to the first aspect.
[0104] According to a fourth aspect, the invention relates to the use of carbon obtainable by the method according to the first aspect as active material in a negative electrode of a secondary battery, such as a lithium ion battery.The carbon according to the fourth aspect may be further defined as set out above in relation to the first aspect.
[0105] The carbon obtained by the method according to the first aspect is preferably used as an active material in the negative electrode of a non-aqueous secondary battery such as a lithium ion battery. Before use in the negative electrode, the carbon is crushed to an average particle size of 3-20 μm. When used to prepare such a negative electrode, any suitable method can be used to form such a negative electrode. In the formation of the negative electrode, carbon can be treated with other components. Such other components may include, for example, one or more adhesives to form carbon into an electrode, a conductive material such as carbon black, carbon nanotubes or metal powder, and / or other Li storage materials such as graphite or lithium. For example, the adhesive may be selected from, but not limited to, poly(vinylidene fluoride), poly(tetrafluoroethylene), carboxymethyl cellulose, natural butadiene rubber, synthetic butadiene rubber, polyacrylate (salt), poly(acrylic acid), alginate (ester), etc., or selected from a combination thereof. Optionally, a solvent such as, for example, 1-methyl-2-pyrrolidone, 1-ethyl-2-pyrrolidone, water or acetone is used during processing.
[0106] Example
[0107] The content of inorganic substances such as aluminum, calcium, iron, potassium, magnesium, manganese, sodium and silicon in the carbonized samples was evaluated by ICP-OES (Inductively Coupled Plasma-Optical Emission Spectrometry). The carbon samples were oxidized with hydrogen peroxide and then wet digested with nitric acid in a microwave oven. The content of inorganic substances was quantified by ICP-OES. The total metal content was calculated by summing up the content of the individual metals.
[0108] Example 1
[0109] Kraft lignin powder from the LignoBoost process was added to heated water (60°C). After that (5 wt. %, based on the dry weight of lignin added to the water) oxalic acid was added and the mixture was stirred at a maintained temperature of 60°C for a period of 4 hours. The mixture was then filtered and the lignin was collected. The above washing process was repeated once more, after which the lignin was collected and dried at 60°C to a moisture content below 5 wt. %.
[0110] The washed lignin powder was agglomerated by roller compaction into particles with a particle size distribution of 0.5-1.5 mm. The agglomerated lignin was slowly heated to up to 230° C. for a period of 2 h in a rotary kiln under air to obtain heat stabilized agglomerated lignin. The heat stabilized agglomerated lignin was then heated to up to 500° C. for a period of 2 h in a rotary kiln under an inert atmosphere to carbonize the lignin and obtain a carbon material.
[0111] The content of inorganics was measured for the lignin starting material (sample 0), after washing in acid (sample 1), and after carbonization (sample 2), and the results from the ICP analysis are summarized in Table 1. The content of inorganics was reduced by the acid washing procedure. The content of inorganics increased when comparing samples 1 and 2 due to the weight loss during the conversion of lignin to carbon.
[0112] Table 1: Inorganic content. “Metal” refers to the total metal content.
[0113]
[0114] In view of the above detailed description of the present invention, other modifications and variations will become apparent to those skilled in the art. However, it should be apparent that such other modifications and variations can be achieved without departing from the spirit and scope of the present invention.
Claims
1. A method for preparing carbon, wherein the method comprises the following steps: i) providing lignin having a total metal content of less than 200 ppm; ii) subjecting said lignin to a heat treatment at one or more temperatures in the range from 300°C and 1500°C, wherein said heat treatment is carried out for a total time of from 30 minutes to 10 hours, to obtain carbon.
2. The method according to claim 1, wherein the lignin provided in step i) has an iron content of less than 15 ppm.
3. The method according to any one of claims 1 or 2, wherein the lignin provided in step i) has a manganese content of less than 10 ppm.
4. The method according to any one of claims 1 to 3, wherein the lignin provided in step i) has an aluminum content of less than 17 ppm; a calcium content of less than 16 ppm; a potassium content of less than 10 ppm; a magnesium content of less than 42 ppm; and a sodium content of less than 30 ppm.
5. The method according to any one of claims 1 to 4, wherein the lignin provided in step i) is kraft lignin.
6. The method according to any one of claims 1 to 5, wherein the lignin is provided in the form of particles and wherein the particle size distribution of the lignin particles is such that at least 80% by weight of the particles have a diameter of less than 0.2 mm.
7. The method according to claims 1-6, wherein the lignin provided in step i) is provided by a method comprising the steps of: a) providing lignin in solid form; b) providing an acidic aqueous solution having a pH below 6; c) immersing the lignin in the acidic aqueous solution for at least 15 minutes, wherein the temperature of the acidic aqueous solution during immersion is in the range of from 40° C. to 100° C., to remove metals from the lignin to the acidic aqueous solution, so as to obtain purified lignin having a total metal content of less than 200 ppm; d) separating the obtained purified lignin from the acidic aqueous solution; and e) optionally washing the separated purified lignin, Therein the lignin remains in solid form during all steps of the process.
8. The method according to claim 7, wherein the total amount of acid in the acidic aqueous solution is in the range from 0.1 to 6 wt% based on the dry weight of lignin immersed in the acidic aqueous solution.
9. The method according to any one of claims 7-8, wherein the acidic aqueous solution comprises at least one organic acid.
10. The method according to claim 9, wherein the at least one organic acid is selected from the group consisting of formic acid and oxalic acid.
11. The method according to any one of claims 7 to 10, wherein the separation in step d) is performed using filtration.
12. The method according to any one of claims 7 to 11, wherein steps cd) and optionally e) are repeated at least once.
13. The process according to any one of claims 7 to 12, wherein the separated lignin is subjected to washing with an aqueous solution.
14. The method according to any one of claims 7 to 13, wherein the method comprises an additional step of drying the separated and optionally washed lignin.
15. The method according to any one of claims 1 to 14, wherein step ii) comprises a preliminary heating step followed by a final heating step.
16. The method according to claim 15, wherein the preliminary heating step ii) is carried out at a temperature between 400°C and 800°C for at least 30 minutes.
17. The method according to any one of claims 15 or 16, wherein the preliminary heating step is performed in an inert atmosphere.
18. The method according to any one of claims 15 to 17, wherein the final heating step is carried out at a temperature between 800°C and 1500°C for at least 30 minutes.
19. The method according to any one of claims 15 to 18, wherein the final heating step is performed in an inert atmosphere.
20. The process according to any one of claims 1 to 19, wherein the carbon obtained has a total metal content of less than 800 ppm.
21. A process according to any one of claims 1 to 20, wherein the carbon obtained has an iron content of less than 60 ppm.
22. A process according to any one of claims 1 to 21, wherein the carbon obtained has a manganese content of less than 40 ppm.
23. The process according to any one of claims 1 to 22, wherein the carbon obtained has an aluminum content of less than 70 ppm; a calcium content of less than 60 ppm; a potassium content of less than 40 ppm; a magnesium content of less than 170 ppm; and a sodium content of less than 120 ppm.
24. Carbon obtained from lignin, wherein the carbon has a total metal content of less than 800 ppm.
25. The lignin-derived carbon of claim 24, wherein the carbon has an iron content of less than 60 ppm.
26. The carbon obtained from lignin according to any one of claims 24 or 25, wherein the carbon has a manganese content of less than 40 ppm.
27. The lignin-derived carbon of any one of claims 24-26, wherein the carbon has an aluminum content of less than 70 ppm; a calcium content of less than 60 ppm; a potassium content of less than 40 ppm; a magnesium content of less than 170 ppm; and a sodium content of less than 120 ppm.
28. A negative electrode for a non-aqueous secondary battery, comprising carbon obtainable by the method according to any one of claims 1 to 23 as an active material.
29. Use of carbon obtainable by a process according to any one of claims 1 to 23 as active material in a negative electrode of a secondary battery.
Citation Information
Patent Citations
Method for extracting lignin from black liquor and products produced thereby
CN105531303A
Method for treating lignin-based material
CN105862484A
Ultrapure kraft lignin composition
US20190241595A1
Carbon materials comprising enhanced electrochemical properties
US9269502B2
Process for producing carbon from heat treated lignin
WO2021250604A1
Cited By
High-rate lignin-based composite hard carbon negative electrode material as well as preparation method and application thereof
CN120270974A
A high-rate lignin-based composite hard carbon anode material, its preparation method and application
CN120270974B
